Effect of alkan-1-ols on the structure of dopc model membrane - Kondela T.; Gallová J.; Hauß T.; Ivankov O.; Kučerka N.; Balgavý P. (Sciendo, 2017)
The effect of general anaesthetics alkan-1-ols (CnOH, where n = 10, 12, 14, 16 and 18 is the number of carbon atoms in the molecule) on the structure of dioleoylphosphatidylcholine (DOPC) model membrane was studied by small-angle neutron scattering (SANS) and small-angle neutron diffraction (SAND). Fluid bilayers were prepared at CnOH:DOPC = 0.3 molar ratio. The results of both the experiments show that bilayer thickness - a thickness parameter dg in the case of SANS and lamellar repeat distance D in the case of SAND - increases with increasing n. A coexistence of two lamellar phases with different D was detected by measuring the C18OH+DOPC oriented sample.